Case Report: Telitacicept in treating a patient with NF155+ autoimmune nodopathy: a successful attempt to manage recurrent elevated sero-anti-NF155 antibodies - Ren, Yijun; Chen, Si; Yang, Huan (Frontiers in Immunology, 2023)
This report presents a case of a neurofascin-155 (NF155)+ autoimmune nodopathy (AN) patient who exhibited resistance to conventional treatments but responded positively to telitacicept therapy. Telitacicept, a dual inhibitor of B lymphocyte stimulator (BLyS) and A proliferation-inducing ligand (APRIL), suppressed the development and survival of plasma cells and mature B cells. The patient's unique clinical features were consistent with NF155+ AN, showing limited response to standard treatments like rituximab and a recurrent significant increase in anti-NF155 antibody titers. Administering telitacicept (160mg, ih) led to an improvement in clinical symptoms, inflammatory neuropathy cause and treatment (INCAT) scale and inflammatory Rasch-built overall disability scale (I-RODS), and stabilized anti-NF155 antibody levels without a rebound. This case demonstrates telitacicept as a potential novel therapy for NF155+ AN, particularly when conventional treatments fail. Further investigation into its safety, efficacy, dosage, and treatment cycle in NF155+ AN is warranted.